Sigma 1 receptor activation improves retinal structure and function in the RhoP23H/+ mouse model of autosomal dominant retinitis pigmentosa. (May 2023) - Barwick, Shannon R.; Xiao, Haiyan; Wolff, David; Wang, Jing; Perry, Elizabeth; Marshall, Brendan; Smith, Sylvia B.
Abstract: Retinitis pigmentosa (RP) is a group of devastating inherited retinal diseases that leads to visual impairment and oftentimes complete blindness. Currently no cure exists for RP thus research into prolonging vision is imperative. Sigma 1 receptor (Sig1R) is a promising small molecule target that has neuroprotective benefits in retinas of rapidly-degenerating mouse models. It is not clear whether Sig1R activation can provide similar neuroprotective benefits in more slowly-progressing RP models. Here, we examined Sig1R-mediated effects in the slowly-progressing Rho P23H/+ mouse, a model of autosomal dominant RP. We characterized the retinal degeneration of the Rho P23H/+ mouse over a 10 month period using three in vivo methods: Optomotor Response (OMR), Electroretinogram (ERG), and Spectral Domain-Optical Coherence Tomography (SD-OCT). A slow retinal degeneration was observed in both male and female Rho P23H/+ mice when compared to wild type. The OMR, which reflects visual acuity, showed a gradual decline through 10 months. Interestingly, female mice had more reduction in visual acuity than males. ERG assessment showed a gradual decline in scotopic and photopic responses in Rho P23H/+ mice. To investigate the neuroprotective benefits of Sig1R activation in the Rho P23H/+ mouse model, mutant mice were treated with a high-specificity Sig1R ligand (+)-pentazocine ((+)-PTZ) 3x/week at 0.5 mg/kg and examined using OMR, ERG, SD-OCT. A significant retention of visual function was observed in males and females at 10 months of age, with treated females retaining ∼50% greater visual acuity than non-treated mutant females. ERG revealed significant retention of scotopic and photopic b-wave amplitudes at 6 months in male and female Rho P23H/+ mice treated with (+)-PTZ. Further, in vivo analysis by SD-OCT revealed a significant retention of outer nuclear layer (ONL) thickness in male and female treated Rho P23H/+ mice. Histological studies showed significant retention of IS/OS length (∼50%), ONL thickness, and number of rows of photoreceptor cell nuclei at 6 months in (+)-PTZ-treated mutant mice. Interestingly, electron microscopy revealed preservation of OS discs in (+)-PTZ treated mutant mice compared to non-treated. Taken collectively, the in vivo and in vitro data provide the first evidence that targeting Sig1R can rescue visual function and structure in the Rho P23H/+ mouse. These results are promising and provide a framework for future studies to investigate Sig1R as a potential therapeutic target in retinal degenerative disease. Highlights: Retinitis pigmentosa (RP) is a group of inherited retinal degenerative diseases that leads to vision loss and blindness. While gene therapy and retinal implants are in progress to slow vision loss due to RP, there is no current cure. The Rho P23H/+ is a clinically relevant model that mimics human adRP making it useful to study therapeutic targets. Rho P23H/+ mice displayed sexual dimorphisms where female visual function and structure degenerate more rapidly than males. Sig1R activation by (+)-PTZ preserved visual function and retinal architecture in the Rho P23H/+ mouse model of adRP.